2021
DOI: 10.1021/acsagscitech.1c00153
|View full text |Cite
|
Sign up to set email alerts
|

Facile Green Synthesis of New Chitosan-Metal Nanoparticles as Nano-Agrofungicide For The Preservation of Postharvest Cherry Fruits

Abstract: In this work, chitosan in citric acid and ascorbic acid along with glucose solutions served as stabilizing and reducing agents of Bi and Zr nanometallic particles, respectively, to produce chitosan-ascorbic acid-bismuth/zirconium (CTS-AA-Bi)/(CTS-AA-Zi), and chitosan-citric acid-bismuth/zirconium (CTS-CA-Bi)/(CTS-CA-Zr) materials. Scanning electron microscopy (SEM) images revealed an irregular sheet-like and round-shaped morphologies attributed to CTS-AA-Bi and CTS-AA-Zr, respectively, with slight agglomeratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Al Abboud studied the antifungal action of biologically produced silver nanoparticles and found that at 80 g/mL, growth inhibition against F. oxysporum was 100%. Nanoparticles possess the ability to break cell membranes and cell walls of fungi, resulting in intracellular component leakage and possible fungi death . Production of reactive oxygen species and hydroxyl radicals could also kill fungal cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al Abboud studied the antifungal action of biologically produced silver nanoparticles and found that at 80 g/mL, growth inhibition against F. oxysporum was 100%. Nanoparticles possess the ability to break cell membranes and cell walls of fungi, resulting in intracellular component leakage and possible fungi death . Production of reactive oxygen species and hydroxyl radicals could also kill fungal cells.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles possess the ability to break cell membranes and cell walls of fungi, resulting in intracellular component leakage and possible fungi death. 79 Production of reactive oxygen species and hydroxyl radicals could also kill fungal cells. QTMC, however, has no discernible antifungal activity against the two plant infections studied.…”
Section: Characterizationmentioning
confidence: 99%
“…While metallic nanoparticles formulated based on chitosan-citric acid-bismuth/zirconium showed significant antifungal activity against Botrytis cinerea in cherry fruits sprayed with these nanoparticles. The treatment with nanoparticles extended the shelf life of the fruits up to 10 days under normal environmental conditions [110].…”
Section: Fruitsmentioning
confidence: 99%